Straight Edge Movement dan Transformasi Sosial dalam Subkultur Underground di Kota Bandung: Analisis Bibliometrik - Kiagus Muhammad Laudy Ramdhani; Elly Malihah Setiadi; Mirna Nur Alia Abdullah (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the development of academic research on the straight edge movement and social transformation within the underground subculture, with a focus on the potential for expanding research in Bandung, Indonesia. A bibliometric approach was employed to map trends, main themes, and research gaps based on the analysis of 413 publications from 2015 to 2025, gathered through Google Scholar. The data were processed using VOSviewer software to generate a term network map illustrating thematic relationships. The findings indicate that academic interest peaked between 2016 and 2020, with key themes including identity, lifestyle, and social transformation. Network visualization identified five thematic clusters, where identity and social transformation were central. However, no direct link between the straight edge movement and social transformation was found, highlighting a significant research gap. This gap is further reinforced by the dominance of Western perspectives in the literature, while local studies, particularly in Bandung, a city with a rich history of subcultures, remain scarce. The study recommends further contextual research to understand the role of the straight edge movement in driving social change in Indonesia, particularly through qualitative approaches involving local communities.